Cytological features of micropapillary and plasmacytoid variants of urothelial carcinoma. Issue 2 (24th October 2019) - Straccia, Patrizia; Martini, Maurizio; Sacco, Emilio; Bassi, Pier F.; Pierconti, Francesco
Abstract: Background: Micropapillary and plasmacytoid variants of urothelial carcinoma (UC) exhibit very aggressive clinical behavior. To date, only a small number of cytology cases have been reported in either of these variants. Herein, we report 15 cases of UC with combined micropapillary and plasmacytoid features based on urine cytology. Methods: We performed a retrospective analysis of all patients with carcinoma of bladder with predominant plasmacytoid and micropapillary histology who had been seen from 2005 to 2017. A total of 15 cases (six cases of plasmacytoid variant and nine cases of micropapillary variant of bladder cancer) with urine specimen were evaluated. The cytomorphological features were compared between two histological variants. Results: Fifteen urine cytology cases with the diagnosis of high‐grade UC were investigated. The ratio man to women was 5:1 with a median age of 79 years (range: 72‐90 years). Single‐cell pattern, flat sheets, three‐dimensional clusters, micropapillae, nuclear grade, cytoplasmic vacuoles, and necrosis, were evaluated in urine samples of micropapillary variant. The cytological features of plasmacytoid are characterized by large, discohesive, isolated tumor cells that have abundant, thick cytoplasm, and eccentrically located, hyperchromatic nuclei with coarse chromatin and inconspicuous nucleoli. Conclusion: It is important to recognize the cytological characteristics of these uncommon but aggressive entities to determine a precise diagnosis. Attention to morphological features, together with clinical history and appropriate immunohistochemical studies may be useful to urologist in pre‐operative planning and may lead to a more aggressive surgical approach.